The Influence of Work Motivation and Work Discipline on Employee Performance at The Depok City Civil Service and Human Resources Development Agency (BKPSDM) - Nauli Chrissensia, Monica; Netty Laura S; Jonny Siagian (Fundamental Management Journal, 2024)
This study aims to uncover the role of work motivation and work discipline in shaping employee performance at the Depok City Personnel and Human Resources Development Agency (BKPSDM), based on various cases related to employee performance. Many cases exhibit symptoms of imbalance. Researchers use Douglas McGregor's theory to describe motivation and utilize both primary and secondary information. The study employs a quantitative data collection approach, analyzing it to achieve an in-depth understanding of the phenomenon by distributing closed questionnaires to 56 respondents. Prior to analysis, the validity and reliability of all instruments are tested. The verified and reliable information is then further analyzed using the t-test correlation test. The objective of this research is to comprehend the influence of work motivation and work discipline on individual employees. The primary objective is to assess the impact of work motivation and overall work discipline on employee performance through F-test analysis. There is a significant correlation coefficient of 0.419 between work motivation and employee performance. Similarly, there is a significant correlation coefficient of 0.324 indicating a strong influence of work discipline on employee performance. Keywords: employee performance, work motivation, work discipline